ANALISIS PENGARUH ELECTRONIC WORD OF MOUTH (e-WOM) TERHADAP PERILAKU KONSUMTIF PHOTOCARD PADA PENGGEMAR KPOP DI APLIKASI X - Br Sembiring, Cyndy Claudya; Arjawa, I Gusti Putu Bagus Suka; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 5 No 1 (2025): JISSOROT, 2025)
The KPop phenomenon that continues to develop into a global culture has not only influenced the music industry but also the consumer behavior of its fans. One form of consumer behavior that often occurs today is the purchase of Photocards. In this digital era, e-WOM is one of the factors that influences purchasing decisions for KPop fans. This study aims to analyze the influence of electronic word of mouth (e-WOM) on the consumer behavior of photocards on KPop fans in the X application. The population in this study were KPop fans in the X Application with a sample of 100 respondents. The sampling technique in this study used nonprobability sampling with a purposive sampling category and data collection through the distribution of questionnaires with gforms distributed through the X application. The data analysis technique used in this study was the Instrument Test, namely the Validity Test and Reliability Test, the Classical Assumption Test, the Simple Linear Regression Test, the T Test, and the Determination Coefficient Test. The results of the t-test at a margin of error of 5% in this study showed 2,689 with a significance value of 0.008 (p <0.05), meaning that there is a significant positive relationship between electronic word of mouth (e-wom) and photocard consumer behavior among KPop fans in application X. The resulting R Square value is 0.541, which means that the influence of electronic word of mouth (e-WOM) on photocard consumer behavior among KPop fans in application X is 54% and 46% is influenced by other factors outside this study.